(untitled) (The Journal of Building and Land Development, 2023)
This paper presents findings of a study that examined the utilization of Family Planning information (FPI) among women living with human immunodeficiency virus (WLWH) in Tanzania. It involved women attending Reproduction and Child Health (RCH) Clinic at Mbagala in Temeke District. Specifically, the study assessed the extent to which WLWH utilise family planning information and services; and explored the challenges WLWH face in accessing information and subsequent utilization of family planning services. The study employed a qualitative case study design. Primary data was collected using in-depth interviews and observations. Findings indicate that the extent of access to family planning varies among WLWH due to the varied socio-economic backgrounds and exposure to sources of FPI. Challenges constraining the utilization of FP include fear of partner disclosure, lack of exposure to FPI due to poor attendance to Care and Treatment Centres (CTC), socio-cultural barriers, misguided beliefs and women’s over-dependence on male partners. The study recommends integrated training for empowering WLWH to access and use multiple sources of information, Healthcare providers to come up with user-friendly information strategies and policy-makers to consider establishing a comprehensive and sustainable community participatory plan for gathering and applying horizontal communication approach in delivering FPI. Key words: Family planning, Family planning information, Reproduction and Child Health, Women living with HIV, and Reproductive health